Choice of Surgical Treatment for Inferior Recurrences of Retinal Detachment under Silicon Oil Tamponade - T. N. Shevalova; A. N. Kulikov; S. V. Churashov (Oftalʹmologiâ, 2025)
Aim: to formulate an algorithm for choosing surgical treatment for inferior recurrence of retinal detachments (RD) in eyes under silicone tamponade depending on the stage of APVR.Materials and methods. This study included the results of surgical treatment of 114 patients with inferior recurrence of RD under silicone tamponade of the vitreous cavity with APVR. Patients were divided into three groups depending on the stage of APVR and into six subgroups depending on the tactics of surgical treatment. The main criteria are achieving anatomical success rate and improving visual outcomes were compared postoperatively.Results. An algorithm for choosing surgical treatment for inferior recurrences of RD under silicone tamponade has been formulated depending on the stage of PPVR: at the initial stage of PPVR — performing only scleral buckling (SB); at an advanced stage of PPVR — performing vitreoretinal surgery in combination with SB; at an advanced stage of PPVR — performing vitreoretinal surgery in combination with retinotomy and short-term postoperative tamponade of the perfluorocarbon liquids.Conclusion. The created algorithm for choosing surgical intervention for inferior recurrences of RRD complicated by PPVR, under silicon oil tamponade depending on the stage of PPVR, allows to improve the anatomical and functional results of treatment.